KEWENANGAN YURIDIS KOMISI PENYIARAN DALAM PENGAWASAN KONTEN PENYIARAN BERBASIS INTERNET TELEVISI DAN RADIO - Priatna, Achmad Nashrudin (LPPM Universitas Bina Bangsa, 2025)
Broadcasting is growing along with the development of communication and information technology. Broadcasting is generally carried out through electronic mass communication media, namely radio and television, which disseminate their broadcasts using radio wave frequencies. Along with the times, broadcasting uses internet-based media to disseminate its broadcasts. However, there are problems requested in the Constitutional Court Decision Number 39/PUU-XVIII/2020, where entrepreneurs engaged in the broadcasting business using the radio frequency spectrum requested that the Broadcasting Law not only be imposed on broadcasting using the frequency spectrum but also on internet-based broadcasting content service providers. In connection with this, this research is aimed at analyzing and knowing the supervisory authority between Internet-Based Broadcasting Content Service Providers and Content Services Through Television and Radio Spectrum Perspective of Positive Law and Constitutional Court Decision No. 39/PUU-XVIII/2020. The research found that the supervisory authority of internet-based broadcasting content service providers is not regulated in ITE Law nor in Broadcasting Law, so the broadcasting code of conduct regulated in Broadcasting Law and derivative regulations issued by KPI cannot reach social media platform broadcasts. Meanwhile, broadcasting content service providers through radio and TV spectrum are carried out by the Indonesian Broadcasting Commission (KPI) which is given the authority to supervise broadcasting institutions.